Robotic Surgery – A Personal View of the Past, Present and Future. (8th May 2015) - Davies, Brian
Research into robotic surgery has been undertaken for over 25 years. In that period a small number of companies have been formed to exploit this research and have undertaken clinical trials on patients. However, far fewer clinical applications have been undertaken than would have been expected from the level of research activity. This paper puts forward a number of reasons for this, many of which are not to do with the technology but are a consequence of the clinical and business environments. Recommendations are provided that will hopefully increase the number of clinical systems being applied. Some predictions are made for the future which should increase the number of commercial systems and thus achieve patient benefits.